EVELOPMENT OF TOOL SEARCHING SYSTEM FOR TOOL CRIB - S N UPADHE; MR. A.S. CHAVAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Most of the medium and large scale manufacturing industries have the larger tool room that is used to provide required tool. The tool finding in these rooms is a tedious task and time consuming also. The problem of keeping track of these valuable tools, of knowing where to locate every tool that has been issued, and getting them back promptly after they have been used, is an important task. Various methods are used for this purpose such as, crib ware method, manual method, tool shark method and mobile method. Each of these methods have their own advantages and limitations, This paper discusses development of new tool searching system by executing limitations of existing methods.